2014
DOI: 10.1007/s11433-014-5562-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thermal-shock cracks in ceramic bars

Abstract: Experimental analysis of the cracking in the ceramics subsequent to water quenching have been conducted to clarify the uncertainties of cracking in the ceramics when subjected to thermal shock. The results here indicate that at the critical point of quench temperature, the crack density and the depth reached the minimum and the maximum limits, respectively. On increase of the quench temperature, the crack density increased rapidly before reaching its saturation point, while the crack depth initially decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Since ceramics are brittle materials, this crack can be speculated as the principal factor that reduces the strength of the ceramic. This phenomenon is the same with the results of Bahr and Xu, they indicated that the cracks on the surface (No. 3 and No.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Since ceramics are brittle materials, this crack can be speculated as the principal factor that reduces the strength of the ceramic. This phenomenon is the same with the results of Bahr and Xu, they indicated that the cracks on the surface (No. 3 and No.…”
Section: Resultssupporting
confidence: 91%
“…The stress is largest on the surface and decays with depth, while the fractal dimension is sensitive to this fine distinction. Previous research has found that, when quenching temperature T just passed critical temperature T c , the crack depth and the crack density have an opposite tendency . That means, although the density of cracks increases at 300°C, the crack depth decreases to a certain extent.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This way of extending the applicable range of the perburbative calculation was shown to be reasonable for the one-flavor case [54]. It has also been shown, for the massless two-flavor case, that the renormalization subtraction point should be taken as a function of the summation of the biquadratic chemical potentials while the additional term not only keeps the thermodynamics self-consistent, but also produces reasonable results [59]. In the present paper, we extend this thermodynamically enhanced perturbative QCD (EPQ) model to the actual SQM with massless up (u) and down (d) quarks plus massive strange (s) quarks.…”
Section: Introductionmentioning
confidence: 77%